KAPASITAS PRODUKSI TAS : STUDI KASUS DI PERUSAHAAN KOREA, PT. KOMITRANDO EMPORIO, YOGYAKARTA (BULAN FEBRUARI-MARET 2013) - , BUNGA WAHYU KARTIKASARI, Yuni Wahid Asrori., S.S.,M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Final project graduating paper entitled \"The Prodaction Capacity of Bags : A Case Study in Korean Company, PT. Komitrando Emporio Yogyakarta (February-March 2013)\" was a report on research conducted during the one-month internship in PT. Komitando Emporio. This graduating paper explained the bag production capacity in PT. Komitrando Emporio in February to March 2013. Through the research conducted, libraries and related data, it was known that PT. Komitrando Emporio, in February to March 2013, produced eleven types of bags, they were: bag-packs, travel bags, trolley bags, gym-sack and so forth. PT. KomitrandoEmporio got order from Adidas Company in Vietnam. The common problem that sometimes occurred was the lacks of maximum numbers of bag production which could result in delays of providing product.